Recompensation of Heart and Kidney Function after Treatment with Peritoneal Dialysis in a Case of Congestive Heart Failure. (17th November 2011) - Kihm, Lars P.; Hankel, Vinzent; Zugck, Christian; Remppis, Andrew; Schwenger, Vedat
Abstract : We report the case of a 57-year-old woman suffering from congestive heart failure. Due to refractory congestions despite optimised medical treatment, the patient was listed for heart transplantation and peritoneal dialysis was initiated. Peritoneal dialysis led to a significant weight loss, reduction of hyperhydration and extracellular water obtained by bioimpedance measurement, and a significant improvement in clinical and echocardiographic examination. Furthermore, residual kidney function increased during the long-term followup, and subsequently peritoneal dialysis was ceased. Pulmonary artery pressure and left ventricular ejection fraction remained stable and the patient did well. This case demonstrates the possibility of treating hyperhydration due to congestive heart failure with peritoneal dialysis resulting in recompensation of both heart and kidney functions.